The Mechanisms of build up the dramatic construction in the films of the world of nature - National Geographic's films as a model- (Al-Academy, 2018)
The subject of research entitled "The Mechanisms of build up the dramatic construction in the films of the world of nature - National Geographic's films as a model" emerges from the importance of the subject of the dramatic construction and its departure from its classic style due to the evolution of the visual presentation and its instruments and the specificity and emergence of a form of television production represented by the films of the world of nature which began to occupy an important space in the map of television and television channels specialized in this subject, which drove the researcher to study the mechanisms of producing the dramatic construction in this kind of film s. This research came in three chapters. The first chapter has included the framework of the research, in which the researcher reviewed its problem, represented by the following question: What are the mechanisms of producing the dramatic construction in the films of the world of nature? and it also addressed the research objectives, its importance and its limits which consist of-14- studying the films of the natural world on the channel of National Geographic - Abu Dhabi - produced in 2017. The second chapter has included the theoretical framework, which came in three sections, the first one is entitled (the dramatic construction and the technical necessity), while the second section is entitled (the components of the dramatic construction), and finally, the third topic dealt with (the mechanisms of producing the dramatic construction - image and sound). The third chapter came under the title of "the research procedures" and it included theresearch methodology and its intentional sample which contained two films (Tiger's Revenge) and (Grizzly Bear Leaves its hibernation) and the reasons behind choosing it, and it also included the tool of the research, which was built through the indicators of the theoretical framework, and was presented to a group of experts to obtain its sincerity and to show the proportion of agreement. This chapter also included the analysis unit and then, the analysis of the sample according to the indicators mentioned above. Finally, most important results and conclusions reached by the researcher